COMPARATIVE LITERARY WORKS, LANGUAGE LEARNING AND CHARACTER BUILDING OF LEARNERS - Samuel Jusuf Litualy; Henderika Serpara (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2021)
This paper aims to express efforts to use comparative literary works as a medium in language learning, and at the same time as a means for the formation of the character of learners. The benefits of comparative literature, among others: (1) as the basis of the study of cross-cultural literary works, (2) as the basis or basis of language skills learning (Sprachfertigkeiten) namely: listening (HÓ§rverstÓ“ndnis-Sprechfertigkeit), reading-writing (LeseverstÓ“ndnis-Schreibfertigkeit), (3) as a means of strengthening character education. As the basis for cross-cultural text studies, comparative literary works can be used to compare cultures between nations. As the basis of language learning, comparative literary works, has a uniqueness that is not possessed by other linguistic teaching materials, because the language of literary works has a connotative characteristic (figurative), contains majas, and prioritizes the characteristics of narrative discourse. Language in literary works prioritizes its main function, which is communicative function and suitable to be used to teach language skills. Furthermore, as a means of strengthening character education, literary works are worthful, which can be used to provide value strengthening for learners as the future generation of the nation.